Risk factors for persistent hypertension in primary aldosteronism after surgery: a systematic review and meta-analysis - Li, Feng; Wan, Chao (Frontiers in Physiology, 2025)
IntroductionThis systematic review and meta-analysis delved into the identification of risk factors associated with persistent hypertension in patients with primary aldosteronism (PA) following surgery.MethodsThrough an exhaustive search across PubMed, Embase, and Cochrane Library databases, 12 studies meeting stringent inclusion criteria were scrutinized.ResultsThe analysis unveiled several significant risk factors contributing to postoperative hypertension persistence in PA patients. Notably, the duration of hypertension emerged as a pivotal predictor, suggesting a correlation between longer preoperative hypertension durations and heightened postoperative hypertension likelihood. Additionally, elevated body mass index (BMI) surfaced as another notable risk factor, accentuating the imperative of weight management interventions in optimizing surgical outcomes. Further, serum potassium levels and estimated glomerular filtration rate (eGFR) were discerned as crucial determinants of postoperative hypertension. Elevated serum potassium levels and diminished eGFR were associated with an augmented risk of persistent hypertension, underscoring the necessity of meticulous preoperative renal function assessment and electrolyte balance management.ConclusionThese findings underscore the paramount importance of preoperative risk assessment and tailored postoperative management strategies to enhance the prognosis and quality of life for PA patients undergoing surgery.